Don Quixote and the Catholic religion - Madrigal, SJ, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The aim of this study is to explore the possibilities of a theological reading of the immortal work of M. de Cervantes, The ingenious Hidalgo don Quixote. For that, firstly, the article presents the debate about the nature of Catholicism by Cervantes, its dependence from Erasmus or its proximity to the Council of Trient (A. Castro, M. Bataillon, M. Unamuno, S. Muñoz Iglesias). Secondly, the author discovers and describes the Don Quixote’s religion and the faith of Alonso Quijano.